Biofunctionalization of synthetic bone substitutes with angiogenic stem cells: Influence on regeneration of critical-size bone defects in an in vivo murine model. Issue 9 (September 2018) - Beger, Benjamin; Blatt, Sebastian; Pabst, Andreas Max; Hansen, Torsten; Goetz, Hermann; Al-Nawas, Bilal; Ziebart, Thomas
Abstract: Purpose: The aim of this study was to investigate the influence of human bone marrow−derived endothelial progenitor cells (EPC) on vascularization and bone regeneration in combination with a bone-substitute material (BSM) in a critical-size bone defect in a murine model. Critical-size bone defects were performed and the defects were filled according to the group membership. Materials and methods: Eighteen rats were randomized in two experimental groups: BSM (BoneCeramic) with/without EPC biofunctionalization, and a control group without BSM and EPC. Calvaria bone defects were performed and the defects were filled according to the group membership. After 8 weeks, qualitative tissue response of newly formed bone mass was analyzed by histology, cone beam CT (CBCT) and micro-CT (μCT) scans. Occurrence of tumor masses due to EPC vascularization in peripheral organs was investigated microscopically in histological slides of liver and kidney. Results: The combination of EPC and BSM showed smaller bone defects in the CT scans and the histological evaluation as the single use of BSM without EPC by trend (p = 0.067). Further, a higher amount of blood vessels could be found in histological slices of BSM in combination with EPC. No inflammatory response or tumor formation could be found. Conclusion: These findings confirm the biocompatibility of the used BSM and provide evidence that the combination of BSM with EPC might be effective for bone vascularization and regeneration. Using EPC in augmentation sites might overall lead to faster and better bone regeneration and should be further investigated in future studies. Highlights: Biofunctionalization of bone substitutes might improve bone regeneration. Endothelial progenitor cells (EPC) have a strong angiogenic potency. Combination of bone substitutes and EPC can accelerate bone regeneration. Combination of bone substitutes and EPC can accelerate bone vascularization. EPC might be suitable for biofunctionalization of bone substitutes.